Effects of zinc oxide and condensed tannins on the growth performance and intestinal health of weaned piglets in ETEC-challenged environment - Yi, Hongbo; Wang, Zhikang; Yang, Bijing; Yang, Xuefeng; Gao, Kaiguo; Xiong, Yunxia; Wu, Qiwen; Qiu, Yueqin; Hu, Shenglan; Wang, Li; Jiang, Zongyong (Frontiers in Microbiology, 2023)
This experiment was conducted to evaluate effects of zine oxide (ZnO) and condensed tannins (CT), independently or in combination, on the growth performance and intestinal health of weaned piglets in enterotoxigenic Escherichia coli (ETEC-K88)-challenged environment. Randomly divided 72 weaned piglets into 4 groups. Dietary treatments included the following: basic diet group (CON), 1,500 mg/kg zinc oxide group (ZnO), 1,000 mg/kg condensed tannins group (CT), and 1,500 mg/kg zinc oxide +1,000 mg/kg condensed tannins group (ZnO + CT). Dietary ZnO supplementation decreased diarrhea rate from 0 to 14 days, 15 to 28 days, and 0 to 28 days (p < 0.05) and no significant on growth performance. The effect of CT on reducing diarrhea rate and diarrhea index was similar to the results of ZnO. Compared with the CON group, ZnO increased the ileum villus height and improved intestinal barrier function by increasing the content of mucin 2 (MUC-2) in jejunum and ileum mucosa and the mRNA expression of zonula occludens-1 (ZO-1) in jejunum (p < 0.05) and the expression of Occludin in duodenum and ileum (p < 0.05). The effects of CT on intestinal barrier function genes were similar to that of ZnO. Moreover, the mRNA expression of cystic fibrosis transmembrane conductance regulator (CFTR) in jejunum and ileum was reduced in ZnO group (p < 0.05). And CT was also capable of alleviating diarrhea by decreasing CFTR expression and promote water reabsorption by increasing AQP3 expression (p < 0.05). In addition, pigs receiving ZnO diet had higher abundance of phylum Bacteroidetes, and genera Prevotella, and lower phylum Firmicutes and genera Lactobacillus in colonic contents. These results indicated that ZnO and CT can alleviate diarrhea and improve intestinal barrier function of weaned pigs in ETEC-challenged environment. In addition, the application of ZnO combined with CT did not show synergistic effects on piglet intestinal health and overall performance. This study provides a theoretical basis for the application of ZnO in weaning piglet production practices, we also explored effects of CT on the growth performance and intestinal health of weaned piglets in ETEC-challenged environment.